The war on drugs and Anglo-American relations: lessons from Afghanistan, 2001-2011 - Berry, Philip A. (Edinburgh Studies in Anglo-American Relations, 2021)
1. Introduction -- Part 1 -- 2. Anglo-American Relations and 9/11 -- 3. The Legacy of Drugs and a Weak State -- Part 2 -- 4. Taliban Drugs on British Streets, 2001-2002 -- 5. Lead Nation on Counter-Narcotics, 2002 -- 6. Counter-Narcotics on the Hoof, 2002-2004 -- Part 3 -- 7. Plan Afghanistan, 2004-2005 -- 8. Afghanistan's Poppy Capital, 2005-2006 -- 9. The Lesser of Two Evils, 2006-2007 -- 10. The Showdown over Aerial Eradication, 2007 -- 11. Counter-Narcotics in Transition, 2008 -- Part 4 -- 12. Obama and Shifting Anglo-American Relations, 2009 -- 13. A Poisoned Chalice, 2009-2011 -- 14. Conclusion -- Appendix: Methodology.